The Design of Signalised Intersections at Area Level. Models and Methods - Gallo, Mariano; De Luca, Giuseppina; D’acierno, Luca (TeMA - Journal of Land Use, Mobility and Environment, 2014)
In this paper the results of the PRIN research project named “Guidelines for the urban transportation network analysis and design: methods and models for designing at area level the signalised intersections” are summarised. In the research project, several problems of signal settings optimisation at area level were studied and some methods and model for optimising the signal setting parameters were proposed. All proposed methods were tested on a real-scale case: the road network of Benevento. The results of the research showed that the proposed methods are able to solve the problem in acceptable computing times also on real-scale networks.